Assessment of complementary feeding practice in children 6-23 months of age in Mosul city - Luay Amjed AL-Waly; Nashwan mustfa AL- Hafidh (College of Nursing,University of Mosul, 2014)
Background and Objectives: Proper feeding practices of children less than 2 years of age is important because it is the most critical period of life for optimal growth and development. This study aims to use the newly developed World Health Organization (WHO) infant feeding Indicators published in 2008, to assess complementary feeding practice in children 6-23 months of age in Mosul city. Materials and Methods: A cross-sectional study was conducted in six primary health care (PHC) centers in Mosul city during 3 months period from 11th of February to 11th of May 2013. The study sample consists of (422) healthy convenient children who attended (PHC) centers for immunization. The questionnaire data filled by the researcher in a direct interview with consent mothers, utilizing the key indicators recommended by the WHO (2008) used to assess infant and young child feeding (IYCF) practices which include minimum dietary diversity, minimum meal frequency and minimum acceptable diet calculated for the age ranges 6 -23 months of age, and based on the mother's recall of foods given to her child in the 24 hours before the interview. The questionnaire subsumed inquires about source of feeding advice practiced by the studied mother. Statistical processing was conducted by the use of version 17 SPSS statistical package. Results: A total of 422 children were enrolled in this study; 231(54.7 %) boys and 191 (45.3%) girls. The mean age of the studied children is 12.4 ± 4.97 months. Less than half 192(45.5 %) of the children 6-23 months of age met the minimum dietary diversity criteria whereas 334(79.1%) met the minimum meal frequency criteria and only 172(40.8%) of the sample achieve the minimum acceptable diet criteria. Grain is the most frequent type of food consumed by 6-23 months aged children followed by dairy products, fruits and vegetables, egg, vitamin A-rich fruits and vegetables, and finally meat and legumes in decreasing frequency. Conclusion: the family was the principal source of advice on child feeding practice. Key words: Complementary feeding, Mosul, new WHO indicators, infant and young child feeding, dietary diversity, meal frequency and minimum acceptable diet.